OPTIMALISASI EVALUASI RANAH AFEKTIF DALAM PENDIDIKAN AGAMA ISLAM: MEWUJUDKAN PEMBELAJARAN BERARTI - Darojat, Umi Sarah Nafi’ah; Hamdani, Saepul; Soraya, Irma (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
Affective domain evaluation in Islamic Religious Education is very important because it is done directly with student behavior. This study aims to determine the implementation of optimizing the evaluation of the affective domain in Islamic Religious Education and the problems faced by Islamic Religious Education teachers in the evaluation. The method used by researchers is a qualitative approach with the type of case approach. The results of this study explain that at Muhammadiyah Elementary School Ponorogo, conducting affective evaluation in four ways, namely first, through observation by observing the attitude of students directly. Second, Islamic Religious Education teachers make journals or student assessment rubrics. Third, students conduct self-assessment. Fourth, with peer assessment. In addition, there are challenges faced by Islamic Religious Education teachers in the implementation of affective domain evaluation, namely students not understanding the material taught, subject matter with abstract indicators, less than maximum time allocation, and uncertain student circumstances.